Investigation of antioxidant and glucometabolic effects of melatonin in experimental diabetes mellitus - Dönder, Emir; Baydas, Giyasettin; Sokmen, Suleman; Erçel, Ergül; Yalniz, Mehmet; Do?an, Halil; Bahçeo?lu, I. Halil (My University, 1999)
Lipid peroxidation is considered as one of the main causes of many complications developing in diabetes mellitus. This study was made in order to determine how the increased lipid peroxidation and the changes in lipid and glucose metabolisms were affected by melatonin injection in diabetes mellitus. Eexperimentally diabetes was induced in rats with streptozocin. Melatonin was given daily and lipid peroxidation of plasma and tissues was detected at the end of the experiment. Malondialdehyde and conjugated dienes (as lipid peroxidation) were measured. Besides, the enzyme activity of glutathion peroxidase, which is among the antioxidant enzymes, was determined. In addition plasma lipid and fatty acid compositions were investigated. In conclusion, it was observed that lipid peroxidation increased in diabetes mellitus and melatonin injection prevented this increase. Especially in the brain and renal tissues, the antioxidant effect of melatonin was very evident. In the melatonin applied group, the decrease of stearic acid, which is one of the fatty acids, shows that the platelet aggregation can be inhibited by melatonin. However, it was determined that melatonin didn't influence the glucose metabolism considerably.
Keywords: Diabetes mellitus; Melatonin; Oxidative stress